Copper-Catalyzed Tandem CN Bond Formation: An Efficient Annulative Synthesis of Functionalized Cinnolines - Ball, Catherine J.; Gilmore, Jeremy; Willis, Michael C. (Angewandte Chemie International Edition, 2012)
Cinn‐tillating synthesis: The combination of a readily available copper catalyst, a simple hydrazide nucleophile, and established difunctionalized building blocks provides a new, flexible route to an under‐developed class of aromatic heterocycles, cinnolines (see scheme).